IMPLEMENTATION OF THE FUNCTIONS OF THE CITY GOVERNMENT IN THE ADMINISTRATION OF PUBLIC SERVICES IN THE HEALTH SECTOR IN THE CITY OF MAKASSAR - Retnosari Budhiasty; Askari Razak; Said Sampara; M. Kamal Hidjaz (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal